PROSES KREATIF BERTEATER PADA MAHASISWA DAN NILAI KARAKTER YANG TERBANGUN DI DALAMNYA - Farid Ibnu Wahid (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
Creative Process of Berteater on Student and Value of Character built in it (Descriptive-Analytical Study of Creative Process of Berteater on Student of Semester VI at Department of Education of Indonesia University of Sultan Ageng Tirtayasa and Its Application in Drama Learning Model in High School). In facing the development of science knowledge and technology with all its positive and negative implications, we need strong fences and strongholds to keep ahlak, character, and personality based on virtue values. Based on the description, an alternative method is needed to organize and develop character education for to respond to the changing times. On the basis of this description, this research tries to offer an alternative method for character planting, especially for the younger generation who will become the heir to continue the nation's sustainability. The method offered, namely the character value recording through the process berteater. This result is based on the assumption that the creative process of the theater will make human beings aware of the process of creation. The result of this research is a new finding about the description of the creative process done by the students of semester VI of the Department of Indonesian Education, University of Sultan Ageng Tirtayasa to provide an alternative method in the cultivation of value- the value of characters through the learning of drama in High School through the creative process berteater.